Parental Polymorphism In Iron- And Zinc-Rich Rice Varieties (Swarna And Type 3) Using Ssr Markers (Applied Biological Research, 2020)
A microsatellite is a specific sequence of DNA bases which contains repeats.  In present study, rice microsatellite (RM)markers were used to study the  parental polymorphism between two parents. The experiment was  conducted at Indian Institute of Rice Research, Rajendranagar Hyderabad (India). ‘Swarna’ and ‘Type 3’ rice varieties dense in grain iron and zinc  were used to study the parental polymorphism. Out of 171 rice markers used  for parental polymorphism, 52 markers showed polymorphism and 119  were monomorphic with expected base pair ranging from 84 to 383 bp.  Therefore, these polymorphic rice microsatellite markers can be used in fine  mapping of iron- and zinc-rich micronutrient genes to study the mapping  populations of crosses obtained from these parents.
Keywords: Biofortification; iron; microsatellite markers; parental polymorphism; rice; zinc